Perceived outcomes of adaptive fitness participation for individuals with physical impairments: An examination of daily and competitive involvement - Torphy, MS, CTRS, Heather; Townsend, PhD, CTRS, CARSS-I, Jasmine; Hawkins, PhD, CTRS, LRT, FDRT, Brent (American Journal of Recreation Therapy, 2021)
Physical activity is an important aspect of a healthy lifestyle and can improve functioning for individuals with physical impairments. One way this is accomplished is through participation in adaptive fitness. This study explored perceived outcomes and experiences associated with daily and competitive involvement in adaptive fitness by individuals with physical disabilities. Individuals were recruited from the 2015 Working Wounded Games (WWGs). Semistructured interviews were conducted with ten participants. Using directed content analysis, six themes emerged, including four themes from daily involvement and two themes from competitive involvement. Results support adaptive fitness as a unique opportunity for individuals with disabilities to engage in a healthy lifestyle by improving their physical, emotional, and social health with increased community involvement. Implications for recreational therapist (RT) practice are discussed.